Analisis Kerusakan Saluran Primer Daerah Irigasi Paya Dapur Kabupaten Aceh Selatan - Fitriani, Irma; Ikhsan, Muhammad; Refiyanni, Meidia (Rifa'Institute, 2022)
Irrigation area Paya Dapur is one of the irrigation areas in South Aceh district. The area of ??irrigation for brackish kitchen has an area of ??about 2390.50 Ha, however, with damage along the channel, the service in water needs is not optimal so that it can be detrimental to farmers. Starting from the collapse of the embankments on the left and right wings, and the blockage of sedimentation channels so that the water supply in the rice fields is not met as needed. The purpose of this study is to determine the physical condition of the building in the primary channel of the kitchen brackish irrigation area and to calculate water efficiency and water loss in the kitchen brackish irrigation area. This research was conducted following the following stages: (1) calculation of irrigation area water efficiency, (2) calculation of irrigation area water loss. From the results of these calculations, it can be seen that the performance of the Paddy Kitchen irrigation area, from the results of the study, there were conditions of the main building with the results of 20, 45% (damaged), carrier channel 40, 75% (damaged), building for/tapping 43, 16% (damaged)., drains 73, 60% (enough), buildings along the drains 25, 10% (damaged), while from the calculation of irrigation canal efficiency it is 63, 20% and water loss is 16, 66%